AI and Language: A Critical Discourse Analysis of Anima Anandkumar's AI TED Talk - Ahmad Vahry Lilam Putra; Fernanto, Hanny Wulandari; Yanwarita, Nabila; Suprayogi (Institut Agama Islam Negeri Palopo, 2024)
This study thoroughly investigates Anima Anandkumar's TED Talk,